THE MODERN CONDITIONS AND THE STRUCTURE OF INTERACTION BETWEEN UNIVERSITIES, STUDENTS AND EMPLOYERS - D. P. DANILAEV; N. N. MALIVANOV (Высшее образование в России)
The higher education system has two customers: employer and student. Their needs are different and even contradictory. Therefore, the new forms of interaction between universities and enterprises are being built during technical specialists’ training. The aim of the article is to analyze the new conditions and the structure of university, student and business interaction in the technician training process. The analysis of external and internal challenges that higher education system faces makes it possible to identify the technical specialists’ training system strengths and weaknesses. It is noted that the condition for its preservation as the main source of enterprise staffing is the organizational structure change of interaction between employers, universities and students. The efficiency, the specialists’ training variability, and the economic feasibility of investment are the criteria for the interaction structure formation. The paper shows the appropriateness of the information environment as a virtual educational environment element. The development potential lies in the involved employers’ range expanding based on the information environment of interaction between enterprises and students, and on the creation of a mutual choice competitive environment both among students and employers.